The rise of 3D-printed firearms - Dass, Rueben Ananthan Santhana (2025)
The recent assassination of the UnitedHealthcare CEO in New York has received widespread media attention over the last week. A notable characteristic of the assassination was the use of an unserialised firearm with 3D-printed components, which has become a growing security concern because of its ease of access and the anonymity it provides.